Validasi Metode Analisis Penetapan Kadar Bahan Baku Lapatinib Ditosylate secara KCKT-DAD - Nopi, Nely Suryani; Isnaeni, Neni (Eruditio : Indonesia Journal of Food and Drug Safety, 2023)
The validation analytical method of the Lapatinib ditosylate assay is crucial to increase testing capability and capacity in strengthening the supervision of post-marketing drugs in Indonesia. A fast, precise, accurate, valid, and efficient test method is needed to carry out the test. A previous study on determining Lapatinib ditosylate assay generally used a C18 column, yet for efficiency, it is also necessary to develop a test method that can use existing resources in the laboratory, where the research used a C8 column. In this study, an analytical method to determine the assay of Lapatinib ditosylate developed using a High-Performance-Liquid Chromatography-Diode Array Detector (HPLC-DAD) system equipped with an autosampler and XBridge ® C8 column (Waters); 250 x 4.6 mm i.d. 5 μm. The mobile phase consisted of pentane-1-sulfonic acid sodium salt 10 mM - acetonitrile (65:35) eluted isocratically at a 0.6 mL/min flow rate. Detection was carried out at a wavelength of 222 nm. The analytical method was validated with test parameters of selectivity, system suitability, accuracy, precision, linearity, detection limit and quantification limit. Results from the validation study demonstrated a retention time of 4.63 minutes, good linear in the concentration range of 0.06 – 0.18 mg/mL with a correlation coefficient and Vx0 of 1.00000 and 0.1%. Test accuracy (% bias) obtained a value of 0.77% with precision (system, method and intermediate) less than 2.0%. The detection and quantification limits were 0.67 µg/mL and 2.02 µg/mL. Based on the research results, it can be concluded that the method developed provides fast, accurate and valid performance. Validation of the Analytical Method for Determining Lapatinib Ditosylate Raw Material Contents using HPLC-DAD.